Lora performance evaluation in coherent Rayleigh fading channel - Ahmad, Yasser Asrul; Abdul Hamid, Muhammad Nasrin Aqil; Abdullah, Khaizuran; Ismail, Ahmad Fadzil (IEEE, 2023)
This research presents an analysis of the performance of a LoraWAN communication system in Coherent channel conditions. The study uses Signal to Noise Ratio (SNR) and Packet Error Rate (PER) performance metrics. The data presented in this research is based on simulations using different values of spreading factors (SF7, SF8, and SF9) and bandwidths (125kHz, and 500kHz). The results show that the trade-off between SF and bandwidth should be considered when choosing the appropriate parameters for the system. The future works that can be done in this research include analyzing the system's performance under different modulation schemes and implementing the system in a real-world scenario.